Pragmatics of convincement : how we deceive with the truth - Loh, Bryan Yih Jing (Nanyang Technological University, 2021)
Paltering is an act that leads others to believe a false implicature by lying with truthful statements. According to studies of this phenomenon, it is commonplace in our daily interactions. The few studies that have been done are based solely on Western society. This inductive study aims to explore the Singaporean environment of lying and tendencies of speakers in natural speech interactions, alongside identifying the various ways in which an utterance can be considered paltering. Fourteen participants (11 males, 3 females) were recruited for this study. A survey questionnaire was issued to obtain opinions on the matter of paltering as part of the first phase of data collection, and then natural conversation data was recorded across several gaming sessions of Among Us (social deception-centric game) via Craig, a native bot in Discord, in the second phase. Participants paltered in these sessions, contrary to some opinions that only experienced liars would do so. The results show that there was a tendency to palter proactively over reactively, presumably due to the desire for self-preservation of image. Other results present a myriad of psychological thought processes, and I theorize how each finding may be explained with existing studies or speculation.